Principal component analysis for field separation - Ton, Tich Ai (H. : ĐHQGHN, 2017)
The article contains different techniques of geophysical data processing by using softqrae Mathematica. Field separation is one of the most important problems in geophysical data interpretation. For potential fields, when there are observational data for the both the profile survey and area survey.